The effect of antioxidant supplementation in the treatment of epilepsy - Nazar A.K. hamid (University of Mosul, 2011)
Aim: To assess serum level of malondialdehyde (MDA) and total antioxidant status (TAS) as a representative of oxidative stress in patients with generalized epilepsy and to evaluate the therapeutic effect of the antioxidant (vitamin E and vitamin C) on the levels of MDA,TAS and frequency of seizures attacks after two months therapy. for a period of two months as a supplementation therapy. Subjects and Methods: The study was conducted in Iben-seena Hospital in Mosul city-Iraq. Fifty three patients with generalized epilepsy were included in this study (32 male and 21 female). The study included 40 apparently healthy subjects, age and sex matched as a control group. Initially from both the patients and controls, blood samples were taken. Another blood samples were taken from the patients 2 months after vitamin E and vitamin C treatment, blood samples were analysed for serum MDA and serum TAS. Result: Serum MDA was found to be significantly higher ( P